Penanaman Nilai Kemandirian Anak Usia Dini Melalui Konsep Sistem Among (Asah, Asih, Asuh) - Siti Wahyuningsih, N.K Dewi, R.Hafidah (Universitas Sebelas Maret, 2019)
The research aims to see the planting of the independence of early childhood through applying the system among. Data was taken at Gugus Mawar Kindergarten and Early Childhood Education, Karanganyar Regency. Data was taken in August 2018. The research subjects were 6 TK and 3 PAUD. Retrieval of data using observation, interview, and documentation techniques. Test the validity of the data using triangulation techniques. Data analysis using interactive models. Data in the field shows that the value of independence in early childhood can be embedded through the system among the concepts applied in the learning process. The concept of the system among those applied is the concept of education where the teacher acts as a facilitator and role model for children. Planting the value of independence through among system concepts can also be applied through habituation in school life..